Optimizing Skeletal Muscle Anabolic Response to Resistance Training in Aging - Endo, Yori; Nourmahnad, Atousa; Sinha, Indranil (Frontiers in Physiology, 2020)
Loss of muscle mass and strength with aging, also termed sarcopenia, results in a loss of mobility and independence. Exercise, particularly resistance training, has proven to be beneficial in counteracting the aging-associated loss of skeletal muscle mass and function. However, the anabolic response to exercise in old age is not as robust, with blunted improvements in muscle size, strength, and function in comparison to younger individuals. This review provides an overview of several physiological changes which may contribute to age-related loss of muscle mass and decreased anabolism in response to resistance training in the elderly. Additionally, the following supplemental therapies with potential to synergize with resistance training to increase muscle mass are discussed: nutrition, creatine, anti-inflammatory drugs, testosterone, and growth hormone. Although these interventions hold some promise, further research is necessary to optimize the response to exercise in elderly patients.